Valproic Acid: A Promising Therapeutic Agent in Glioma Treatment - Han, Wei; Guan, Wei (Frontiers in Oncology, 2021)
Glioma, characterized by infiltrative growth and treatment resistance, is regarded as the most prevalent intracranial malignant tumor. Due to its poor prognosis, accumulating investigation has been performed for improvement of overall survival (OS) and progression-free survival (PFS) in glioma patients. Valproic acid (VPA), one of the most common histone deacetylase inhibitors (HDACIs), has been detected to directly or synergistically exert inhibitory effects on glioma in vitro and in vivo. In this review, we generalize the latest advances of VPA in treating glioma and its underlying mechanisms and clinical implications, providing a clearer profile for clinical application of VPA as a therapeutic agent for glioma.